Susceptibility of Aedes aegypti to temephos and cypermethrin insecticides, Brazil - Luna, Jonny E Duque; Martins, Marcos Ferrer; Anjos, Adriana Felix dos; Kuwabara, Eduardo Fumio; Navarro-Silva, Mário Antônio (Revista de Saúde Pública, 2004)
Bioassays were performed in order to detect the susceptibility of Aedes aegypti to the chemical insecticides temephos and cypermethrin. The results showed that this species is susceptible to temephos and presents resistance to cypermethrin.